HLH as an additional warning sign of inborn errors of immunity beyond familial-HLH in children: a systematic review - Ricci, Silvia; Sarli, Walter Maria; Lodi, Lorenzo; Canessa, Clementina; Lippi, Francesca; Dini, Donata; Ferrari, Marta; Pisano, Laura; Sieni, Elena; Indolfi, Giuseppe; Resti, Massimo; Azzari, Chiara (Frontiers in Immunology, 2024)
Background Hemophagocytic Lymphohistiocytosis (HLH) is a rare and life-threatening condition characterized by a severe impairment of the immune homeostasis. While Familial-HLH (FHL) is a known cause, the involvement of other Inborn Errors of Immunity (IEI) in pediatric-HLH remains understudied. Objective This systematic review aimed to assess the clinical features, triggers, laboratory data, treatment, and outcomes of pediatric HLH patients with IEI other than FHL (IEInotFHL), emphasizing the importance of accurate identification and management. Methods A systematic search for studies meeting inclusion criteria was conducted in PubMed, EMBASE, MEDLINE, and Cochrane Central. Quality assessment was performed through JBI criteria. Results A comprehensive search yielded 108 records meeting inclusion criteria, involving 178 patients. We identified 46 different IEI according to IUIS 2022 Classification. Combined immunodeficiencies, immune dysregulation disorders, and phagocyte defects were the IEI most frequently associated with HLH. In 75% of cases, HLH preceded the IEI diagnosis, often with an unrecognized history of severe infections. Triggers reflected the specific infection susceptibilities within IEI groups. Liver and central nervous system involvement were less common than in FHL cases. Treatment approaches and outcomes varied, with limited long-term follow-up data, limiting the assessment of therapeutic efficacy across IEI groups. Conclusion A comprehensive evaluation encompassing immunological, infectious, and genetic aspects is essential in pediatric-HLH. Relying solely on FHL or EBV susceptibility disorders tests is insufficient, as diverse other IEI can contribute to HLH. Early recognition of HLH as a potential warning sign can guide timely diagnostic investigations and facilitate tailored therapeutic interventions for improved outcomes. Systematic review registration https://www.crd.york.ac.uk/prospero/display_record.php?RecordID=371425, PROSPERO, CRD42022371425.